Implementation of Civic Education in Increasing Religious Tolerance in Elementary Schools in the 21st Century - Muhammad Haris; Hidayatul Mufidah (CV. Media Digital Publikasi Indonesia, 2025)
In the era of increasing globalization, the diversity of cultures and religions in Indonesia presents significant challenges for the education system. Religious tolerance, a crucial aspect of fostering a harmonious and civilized society, must be instilled from an early age. Civic Education (PKn) at the elementary school level plays a key role in this process, as its curriculum aims to cultivate responsible citizens who respect differences and can coexist peacefully with others of varied backgrounds. Despite various policies and programs aimed at promoting tolerance, incidents of intolerance among youth persist, indicating that current educational approaches may not be fully effective. This research seeks to evaluate and analyze the implementation of PKn in enhancing religious tolerance at the elementary school level, focusing on teaching methods and student engagement. Using a literature review with a critical analysis approach, the study examines books, journal articles, research reports, and policy documents related to PKn and religious tolerance. The findings reveal that PKn is effective in instilling tolerance values, though challenges such as inadequate teacher training and resource limitations hinder its full potential. The study concludes with recommendations for improving PKn implementation to better address the needs of the 21st century, emphasizing the need for a collaborative effort among government, schools, and families to support a more inclusive educational environment. This research underscores the importance of refining PKn practices and offers a foundation for future studies on civic education and religious tolerance.